EDUCATIONAL TASKS IN THE PRIMARY CLASS ARE A TOOL FOR DEVELOPING STUDENTS' HEURISTIC SKILLS - Rustam KHURRAMOV (Scholar Express Journal, 2022)
This article was prepared on the basis of the innovations in our country regarding the further development of students' heuristic abilities in primarygrade native language classes, as well as several proposals aimed at solving this problem and increasing the effectiveness of the educational process. The article also provides specific solutions to increase the quality indicators of efficiency
Keywords: Methodology; heuristic; creative; technology